2019
DOI: 10.1002/jcsm.12395
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/IGF1 signalling mediates the effects of β2‐adrenergic agonist on muscle proteostasis and growth

Abstract: Background Stimulation of β 2 ‐adrenoceptors can promote muscle hypertrophy and fibre type shift, and it can counteract atrophy and weakness. The underlying mechanisms remain elusive. Methods Fed wild type (WT), 2‐day fasted WT, muscle‐specific insulin (INS) receptor (IR) knockout (M‐IR −/− ), and MKR mice were studied with regard to acute effects of the β 2 ‐agonist formoterol (FOR) on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 75 publications
(182 reference statements)
5
39
0
2
Order By: Relevance
“…Because CGRP was found to control AChR abundance at the plasma membrane of differentiated myotubes independent of protein synthesis [16], our current and previous data [38] suggest that the ability of CGRP to prevent NMJ degeneration in the setting of DEN is due to the activation of mTORC1, leading to reduced autophagy and AChR degradation. The fact that CGRP activates mTORC1 but does not stimulate protein synthesis is consistent with recent studies, which demonstrated that mTORC1 can inhibit autophagy independent of the control of protein synthesis [68], [69]. Mechanistically, the full activity of mTORC1 depends on its lysosomal localization mediated by the Ragulator-Rag complex [70], [71] followed by its interaction with Rheb [71], a key activator of mTORC1 stimulated by insulin [69].…”
Section: Discussionsupporting
confidence: 88%
“…Because CGRP was found to control AChR abundance at the plasma membrane of differentiated myotubes independent of protein synthesis [16], our current and previous data [38] suggest that the ability of CGRP to prevent NMJ degeneration in the setting of DEN is due to the activation of mTORC1, leading to reduced autophagy and AChR degradation. The fact that CGRP activates mTORC1 but does not stimulate protein synthesis is consistent with recent studies, which demonstrated that mTORC1 can inhibit autophagy independent of the control of protein synthesis [68], [69]. Mechanistically, the full activity of mTORC1 depends on its lysosomal localization mediated by the Ragulator-Rag complex [70], [71] followed by its interaction with Rheb [71], a key activator of mTORC1 stimulated by insulin [69].…”
Section: Discussionsupporting
confidence: 88%
“…Binding of ␤2 agonists to the receptor activates adenylate cyclase with generation of cyclic AMP and activation of protein kinase A (PKA). Chronic treatment with ␤2 agonists as clenbuterol leads to muscle hypertrophy through still poorly defined pathways, which appear to involve the IGF1-PI3K-Akt-mTOR cascade [18,19]. The role of PKA-dependent phosphorylation of the transcription factor CREB (cAMP response element binding protein) and associated coactivators in mediating muscle hypertrophy is not known, although the pro-hypertrophic factor MEF2 (see below) could be involved, as a dominant-negative CREB in postnatal mouse muscles caused muscle wasting that was associated with reduced expression of MEF2 target genes [see 20].…”
Section: β2-agonistsmentioning
confidence: 99%
“…This effect is facilitated by Akt/mTOR signaling as treatment with rapamycin abolishes this effect [ 39 ]. Recent studies have demonstrated that β2-adrenergic signaling impinges on insulin/IGF-1 receptor signaling [ 40 ], where genetic or pharmacological inhibition of the insulin or IGF-1 receptor abolishes the anti-proteolytic effect of β2-adrenergic agonists. Interestingly, formoterol also induces the expression of JunB, a transcription factor that promotes muscle hypertrophy independently of mTOR [ 41 ].…”
Section: Regulators Of Protein Synthesismentioning
confidence: 99%